Deglacial and postglacial sedimentary architecture in a deeply incised paleovalley-paleofjord--The Pennsylvanian (late Carboniferous) Jejenes Formation, San Juan, Argentina - Dykstra, Mason (2006)
Quebrada de las Lajas, near San Juan, Argentina, preserves an early Pennsylvanian deglacial-postglacial succession in a highly confi ned paleofjord setting. The sedimentary succession records four distinct stages in the evolution of the valley fi ll. Stage 1 is represented by the deposits of subglacial diamictites, ice-contact deltas, and related deepwater lacustrine environments, including several subaqueous channels. Stage 2 records a glacio-eustatic marine transgression, and a slow-down of the clastic supply into the paleofjord. Stage 3 records a sandy, confi ned turbidite environment. Stage 4 consists of a coarse-grained delta, which represents a signifi cant rejuvenation of the sedimentary system in the paleofjord. The transition from stage 1 to stage 2 was abrupt and basinwide, and has proven to be a good regional correlation marker. In this paleovalley, the glacioeustatic rise probably caused fl oating and consequent rapid melting of the valley glacier. This resulted in a paleovalley-wide turbidite event that is up to 5 m thick and indicates an overall waning character. The rapid sediment emplacement in this event and resulting loading of the paleovalley sediments may have helped cause widespread mass-transport events at the stage 1–2 boundary. All stages show evidence of mass-transport–related deposits, but stage 1 records the most widespread mass transport, with a large spectrum of processes represented, including coherently slumped material, rafted blocks, and completely mixed debris-fl ow deposits. These mass-transport deposits range from a few meters to over 50 m thick, and up to hundreds of meters wide and long. Most of the large mass-transport deposits in the lower part of the fjord fi ll occurred at the transition to stage 2, implicating a rise in relative sea level as a possible trigger for the slope failures. Additionally, stage 3 deposits were affected by several thrust-sense dislocations that have large offsets relative to the scale of the sedimentary succession (tens to over 50 m vertically and hundreds of meters laterally); strata associated with the dislocations exhibit growth, indicating very early movement, and they are interpreted as the frontal ramp zones of mass-transport deposits. The abundance and size of mass-transport deposits in stages 1 and 3 helped control sediment pathways throughout the paleofjord.